Correlation between Different Erythrocytes Sedimentation Rates and Bioimpedances Surface Acoustic Wave - Eldosoky, Mohamed (British Journal of Healthcare and Medical Research, 2016)
RBCs with their shapes, volumes and concentrations are very important indicators for the normal and abnormal healthy body. Plasma had electrical characteristics different from the red blood cells. Consequently, the impedance of the plasma- RBCs is proportional to the number or the volume of the RBCs with the plasma. This paper had presented new proposed method for classification of the RBCs by using surface acoustic wave and the bioimpedance so it can be called bioimpedance surface acoustic wave.